2005
DOI: 10.1016/j.imlet.2004.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-5 reduces the expression of uteroglobin-related protein (UGRP) 1 gene in allergic airway inflammation

Abstract: Airway inflammation is thought to play a major role in the pathogenesis of bronchial asthma. The precise role of individual inflammatory cells, mediator and asthma related genes in allergic lung diseases is not completely understood. The uteroglobin-related protein (UGRP) 1 was proposed to be an asthma candidate gene and play a role in regulating lung inflammation, however its precise function in the airways remains obscure. In this investigation, we used a mouse model of allergic airway inflammation to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 42 publications
(58 reference statements)
1
31
0
Order By: Relevance
“…Female BALB/c mice (6 wk old; 6-8 mice/group) were sensitized and challenged with ovalbumin (OVA) as previously described (8,9). All experiments were performed according to the Using Animals in Intramural Research Guidelines (NIH Animal Research Advisory Committee, National Institutes of Health, Bethesda, MD) and approved by the Institutional Animal Care and Use Committee.…”
Section: Animal Model and Adenoviral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female BALB/c mice (6 wk old; 6-8 mice/group) were sensitized and challenged with ovalbumin (OVA) as previously described (8,9). All experiments were performed according to the Using Animals in Intramural Research Guidelines (NIH Animal Research Advisory Committee, National Institutes of Health, Bethesda, MD) and approved by the Institutional Animal Care and Use Committee.…”
Section: Animal Model and Adenoviral Infectionmentioning
confidence: 99%
“…The reduced UGRP1 mRNA levels in the lungs were inversely correlated with increased levels of IL-5 and IL-9 in bronchoalveolar lavage (BAL) fluid obtained from allergic model mice (8,9). Intranasal instillation of IL-5 or IL-9 to naive mice reduced UGRP1 mRNA levels in the lung, suggesting that IL-5 or IL-9 may directly or indirectly mediate UGRP1 gene expression in the lung (8,9). Further, in a Japanese population of adult patients with asthma, a polymorphism (G/A) was identified at Ϫ112 bp of the human UGRP1 gene promoter that was associated with an increased risk of bronchial asthma (5).…”
mentioning
confidence: 99%
“…SCGB1A1, the prototypical protein of this superfamily, also called uteroglobin or Clara cell secretory protein, was proposed as a novel cytokine (13). On the basis of several lines of evidence, SCGB3A2 was proposed to play a role in lung inflammation (11,(14)(15)(16)(17)(18). In fact, we have reported that intranasal administration of recombinant adenovirus expressing SCGB3A2 suppresses the allergen-induced lung inflammation in a mouse model for allergic airway inflammation (19).…”
mentioning
confidence: 99%
“…In the lung, OSM induces inflammation through eosinophil infiltration (24), and strongly elevates expression of TIMP-1, matrix metalloproteinase (MMP)-1, and MMP-9 in fibroblasts that are involved in remodeling of extracellular matrix (18,35,36), suggesting the importance of OSM in lung inflammation. Previously, SCGB3A1 and SCGB3A2 were suggested to be involved in lung inflammation (1,2,(12)(13)(14)(15). In fact, a suppressive role of SCGB3A2 in lung inflammation was demonstrated using recombinant adenovirus expressing SCGB3A2 that was intranasally administered to a mouse model for allergic airway inflammation (16).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the Th2 cytokines IL-4 and IL-13 induce SCGB3A1 expression, suggesting that this gene may potentially play a role in the pathogenesis of inflammatory lung diseases (12). In this respect, the involvement of SCGB3A2, a homologous gene to SCGB3A1, in lung inflammation has been described; proinflammatory cytokines IL-5 and IL-9 reduce SCGB3A2 expression (13,14), whereas anti-inflammatory cytokine IL-10 enhances expression (15). Further, SCGB3A2 suppresses lung inflammation in mice when examined using an allergic airway inflammation mouse model in which recombinant adenovirus-expressing SCGB3A2 is intranasally administered (16).…”
mentioning
confidence: 99%